Here There Be (Dusty) Monsters: High-redshift Active Galactic Nuclei Are Dustier than Their Hosts - Madisyn Brooks; Raymond C. Simons; Jonathan R. Trump; Anthony J. Taylor; Micaela B. Bagley; Bren Backhaus; Kelcey Davis; Véronique Buat; Nikko J. Cleri; Alexander de la Vega; Steven L. Finkelstein; Michaela Hirschmann; et al. (The Astrophysical Journal)
JWST spectroscopy has discovered a population of z  ≳ 3.5 galaxies with broad Balmer emission lines and narrow forbidden lines that are consistent with hosting active galactic nuclei (AGN). Many of these systems, now known as “little red dots,” are compact and have unique colors that are very red in the optical/near-infrared and blue in the ultraviolet. The relative contribution of galaxy starlight and AGN to these systems remains uncertain, especially for the galaxies with unusual blue+red spectral energy distributions. In this work, we use Balmer decrements to measure the independent dust attenuation of the broad and narrow emission-line components of a sample of 29 broad-line AGN identified from three public JWST spectroscopy surveys: CEERS, JADES, and RUBIES. Stacking the narrow components from the spectra of 25 sources with broad H α and no broad H β results in a median narrow H α /H β = $2.4{7}_{-0.05}^{+0.05}$ (consistent with A _v  = 0) and broad H α /H β >8.85 ( A _v  > 3.63). The narrow and broad Balmer decrements imply little to no attenuation of the narrow emission lines, which are consistent with being powered by star formation and located on larger physical scales. Meanwhile, the lower limit in the broad H α /H β decrement, with broad H β undetected in the stacked spectrum of 25 broad H α AGN, implies significant dust attenuation of the broad-line emitting region that is presumably associated with the central AGN. Our results indicate that these systems, on average, are consistent with heavily dust-attenuated AGN powering the red parts of their SED, while their blue UV emission is powered by unattenuated star formation in the host galaxy.